The Glycine max Conserved Oligomeric Golgi (COG) Complex Functions During a Defense Response to Heterodera glycines - Lawaju, Bisho Ram; Niraula, Prakash; Lawrence, Gary W.; Lawrence, Kathy S.; Klink, Vincent P. (Frontiers in Plant Science, 2020)
The conserved oligomeric Golgi (COG) complex, functioning in retrograde trafficking, is a universal structure present among eukaryotes that, maintainsing the correct Golgi structure and function. The COG complex functions in retrograde trafficking occurring between the Golgi cisternae, playing important roles in the homeostasis of enzyme glycosylation. The COG complex is composed of 8 subunits coalescing into two sub-complexes. COGs1-4 compose Sub-complex A. COGs5-8 compose Sub-complex B. The COG complex interacts with the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) that functions with N-ethymalemide sensitive factor (NSF/Sec18p) and -SNAP (Sec17p), effecting membrane fusion. The observation that COG interacts with the syntaxin, suppressors of the erd2-deletion 5 (Sed5p), is noteworthy because Sed5p also interacts with Sec17p (-SNAP). The -SNAP gene . Several copies of the Glycine max (soybean) -SNAP gene are is located within the major Heterodera glycines (soybean cyst nematode, SCN) resistance locus (rhg1) and functions in resistance. The study presented here provides a functional analysis of the G. max COG complex. The analysis has identified 2 paralogs of each COG gene. Functional transgenic studies demonstrate at least one paralog of each COG gene family functions in G. max during H. glycines resistance. Furthermore, treatment of G. max with the bacterial effector harpin, known to function in effector triggered immunity (ETI), leads to the induced transcription of at least one member of each COG gene family that has a role in H. glycines resistance. In some instances, altered COG gene expression changes the relative transcript abundance of regulates syntaxin expression31. These results indicate that the G. max COG complex functions through processes involving ETI leading to H. glycines resistance.